AN INTERNATIONAL SURVEY ON FACTORS AFFECTING SELF- EMPLOYMENT INTENTIONS AMONG STUDENTS OF AGRICULTURE AND LIFE SCIENCES - Juraćak, Josip; Marković, Todor; Majewski, Edward; Moravčikova , Danka; Kokot, Željko (Economics of Agriculture, 2022)
In this study, we investigated the dependence of self employment intention (SEINT) level in agricultural students from Croatia, Poland, Slovakia and Serbia on selected personal traits and country macroeconomic indicators. The results show that the SEINT level depends on student’s perceived desirability of self-employment and perceived self-effcacy. Previous experience with entrepreneurship also affects SEINT. In terms of macroeconomic indicators, higher GDP per capita has been shown to have a positive effect on SEINT, while unfavorable conditions of starting a business have a negative impact. Students from Novi Sad (Serbia) showed higher average SEINT level compared to students from Croatia (Zagreb) and Slovakia (Nitra).